2018
DOI: 10.36076/ppj.1.2018.83
|View full text |Cite
|
Sign up to set email alerts
|

Dual Site Pudendal Nerve Infiltration: More than Just a Diagnostic Test?

Abstract: Background: Pudendal neuralgia (PN) is a very painful and often disabling condition in which pudendal nerve blocks play an important role in both the diagnosis and management of PN. Some previous reports have advocated the use of pudendal nerve infiltration (PNI) as a diagnostic test only. Objective: We aim to assess the outcomes of patients with typical refractory PN who underwent dual site computed tomography (CT)-guided pudendal nerve infiltration. Study Design: A bicentric, retrospective cohort analysis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Although, PNI is commonly used for diagnostic purposes [11,35], it may also be performed as a therapeutic procedure in patients with refractory PN [6]. According to our study, it was observed that patients who underwent pudendal nerve block had significant pain relief for a long period in both groups.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Although, PNI is commonly used for diagnostic purposes [11,35], it may also be performed as a therapeutic procedure in patients with refractory PN [6]. According to our study, it was observed that patients who underwent pudendal nerve block had significant pain relief for a long period in both groups.…”
Section: Discussionsupporting
confidence: 49%
“…Similar to our results, Fanucci et al [9] showed an improvement in pain intensity in 92.6% of patients using CT-guided PNI at the 6-month follow-up. Another previous study reported the efficacy of the CT-guided technique with a mean VAS score of 3.2 at the 6-month follow-up [6]. However, the CT-guided technique requires a radiologic facility and an experienced radiologist, and it exposes the patient to radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pain evaluation was made using simple scoring methods (VAS and SRI scores) which are subjective. 59 …”
Section: Treatmentmentioning
confidence: 99%
“…However, we prefer CT-guided pudendal nerve blocks with injection into the sacrospinous ligament and Alcock's canal. A retrospective review of 95 patients who underwent CT-guided injection of both locations using a combination of lidocaine hydrochloride, ropivacaine chlorhydrate, and cortivazol demonstrated clinical success as defined by at least a 50% reduction in baseline pain scores in 63% of patients at 1-month postprocedure, 50% of patients at 3 months, and 25% of patients at 6 months with no major complications [87]. The efficacy of using steroids in nerve injection was investigated in a randomized, double-blind, controlled study comparing CT-guided pudendal nerve blocks with a local anesthetic versus local anesthetic and corticosteroid.…”
Section: Pudendal Nerve Blockmentioning
confidence: 99%